Experimental study on electrical and thermal performance and heat transfer characteristic of PV/T roof in summer. (5th November 2019) - Shao, Nina; Ma, Liangdong; Zhang, Jili
Highlights: A novel PV/T roof is proposed. The integration of refrigerant-based PV/T component and roof is designed. The performance evaluation index of PV/T roof is analyzed. The heat transfer characteristic of PV/T roof is experimentally investigated. The PV/T roof shows remarkable energy-saving effect in summer. Abstract: A novel PV/T roof is proposed, which functions as the building's external surface, electricity generator and evaporation for heat pump system. It generates electricity and heat for direct use by building. This paper is intended to investigate the experimental performance of the proposed PV/T roof, including electrical, thermal and overall efficiency, as well as heat transfer mechanism. The work was carried out though introduction of system component, experimental platform construction, performance evaluation index analysis, field-testing and performance analysis. It was found that electricity and heat production had similar variation tendency with solar radiation; electrical efficiency was relatively steady, while thermal efficiency was opposite to the variation of solar radiation. During operation, the average electrical, thermal and overall efficiency was 7.2%, 69.3% and 86.8%, respectively. In the aspect of heat transfer, the PV/T roof played a role of shading and surface heat source during daytime and insulation at night, and it showed remarkable energy-saving effect, reducing heat gains, and cooling and heating load by 39.9% and 38.6%, respectively. The research not only provides theoretical support for the design of thermal engineering of a PV/T roof, but also provides an important reference value for the popularization and application of BIPV/T.